Re-Engaging Young People with Education The Steps after Disengagement and Exclusion - Edwards, Simon (Springer International Publishing, 2018)
This book examines how young people can be re-engaged with schooling and their own learning beyond the school gates. Despite attempts by successive UK governments to promote engagement with education, there has been a substantial increase in formal and informal exclusions from secondary schools, particularly of underperforming students who come from low income families. The book builds on an ethnographic study carried out in a youth centre based on a secondary school site, exploring the social and cultural worlds of fourteen students as they complete a GCSE teamwork assessment. Analysing the 'translation' process of the students as they relocate their understanding of teamwork into the language of assessment, the author posits that student identity is a holistic individual project, where knowledge is produced within the conditions for the production of the self-narrative. This volume calls to educators to recognise the importance of relational pedagogy rooted in social practices, rather than individual cognitive performance. It is sure to be of value and interest to students and scholars of exclusion in education and relational pedagogy, as well as practitioners and policy makers.